Reconfiguring Religious Authority in the Digital Age: an Analysis of Lay Preaching in Indonesian Muslim Society - Ardiansyah, Al Fiqri; Tambunan, Marhamah Annazah; Muttaqin, Fakih Fadilah; Ashani, Sholahuddin (MUHARRIK: Jurnal Dakwah dan Sosial, 2025)
This article analyzes the reconfiguration of religious authority within the Indonesian digital ecosystem thru a study of three non-traditional da'wah figures: Syifa Nurfadhilah, Ning Umi Laila, and Akri Patrio. The three represent a new model of religious authority not based on scholarly lineage or formal institutions, but rather formed thru digital performativity, emotional narratives, and the active engagement of audiences on social media. This research uses a qualitative approach with digital content analysis and a study of audience interaction in the comment section as the primary data. The research findings indicate that religious legitimacy now operates as "authority from below," formed participatorily thru mechanisms of affection, psychological identification, and social and algorithmic capital. Syifa presents a narrative-based authority on healing and self-love that resonates with young women; Ning Umi Laila bridges pesantren traditions with digital culture thru humor and warmth; while Akri Patrio converts celebrity reputation into dakwah credibility. This finding supports the thesis that the mediatization of religion has led to the fragmentation and pluralization of authority, and shows a shift in da'wah from institutional spaces to open, horizontal digital arenas heavily influenced by platform logic. This article recommends the need to reorient traditional da'wah strategies to remain relevant amidst an increasingly digitalized and democratized religious landscape.